The Impact of Media Literacy Intervention on the Students\' Attitudes about Self-Medication of Slimming Supplements - Mahnaz Solhi; Hanieh Jormand; Mahmoudreza Gohari (Mashhad University of Medical Sciences, 2016)
Background and objective: Self-medication of slimming supplements has increased. Media advertising is involved in this field. The aim of the present study was to determine the effect of media literacy educational intervention in the students' attitudes about self-medication of slimming supplements among the female dormitories in University of Medical Sciences in Iran. Methods: In this quasi-experimental study of controlled type, 98 students were selected by multistage cluster sampling method and randomly divided into two groups of 49 tests and 49 control. The data collecting instruments were the researcher-made questionnaire about media literacy and attitude on self-medication of slimming pills, BICI questionnaire of body image, and SEI Cooper Smith's questionnaire of self-esteem. Based on the results obtained from the questionnaires early completion, an appropriate educational intervention was designed and carried out. One and three months after the intervention, data was gathered and analyzed in (16) SPSS software using descriptive and analytical tests. Results: Before the intervention, the mean scores of attitude, body image, self-esteem, and dimensions of media literacy in both groups were moderate, and there was no significant difference between them. Also, positive correlations were observed in the experiment group between attitude and knowledge (r = 0.99, p = 0.001), critical thinking (r = 0.61, p = 0.001) and analysis (r=0.37, p=0.009). One and three months after the intervention, the mean scores of  body image, self-esteem, and dimensions of media literacy were  observed significant in  both groups (p <0.05). Conclusion: Media literacy education was effective in promoting the attitude about slimming supplements. Paper Type: Research Article.